The Influence of Influencer Marketing, Online Customer Reviews, and Price on Purchase Intention of Oh My Glam (Omg) Beauty Products on Shopee E-Commerce (Study on Generation Z in Surabaya City) - Aulya Difta Yasah; Siti Ning Farida (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The rapid growth of the beauty industry in Indonesia’s e-commerce sector is driving competition among cosmetic brands, including the local brand Oh My Glam (OMG). In this context, companies need to understand the factors that can increase consumers’ purchase intention. This study aims to analyze the influence of influencer marketing, online customer reviews, and price on purchase intention for Oh My Glam (OMG) Beauty products on the Shopee e-commerce platform among Generation Z in Surabaya. Using an associative quantitative method, the study sample consisted of 157 respondents obtained through non-probability sampling using a questionnaire as the research instrument. Data analysis was performed using multiple linear regression via SPSS 25. The data analysis techniques used included a research instrument test, classical assumption tests, multiple linear regression analysis, a coefficient of determination (R²) test, an F-test, and a t-test. The results indicate that Influencer Marketing, Online Customer Reviews, and Price simultaneously have a significant effect on purchase intention for Oh My Glam (OMG) products. Influencer Marketing has a partial, positive, and significant influence on purchase intention for Oh My Glam (OMG) products. Online Customer Reviews have a partial, positive, and significant influence on purchase intention for Oh My Glam (OMG) products, and price has a partial, positive, and significant influence on purchase intention for Oh My Glam (OMG) products.